Response of Indian Mackerel (Rastrelliger kanagurta) Biomass Size-Spectra Towards Moon Phase - Hutubessy, Barbara Grace; Mosse, Jacobus Wilson; Bahari, Muthia; Aome, Dyah (Aquaculture Department, University of Mataram, 2025)
Lift net is one of light fishing which is occupied to catch small pelagic species. Plenty of studies on lift net have been presented but very view has explored at the biomass size spectrum of Indian Mackerel as a description of fishing intensity and selectivity. Indian Mackerel (Rastrelliger kanagurta) is among other small pelagic species captured by lift net. Observation of biomass size spectrum under different environmental factors aims to describe the selectivity of Indian Mackerel towards lift nets operated at Waralohi waters, Western Seram Regency. Length (cm) and weight (gr) of fish were used to calculate biomass size spectrum. Length of fish ranged from 16.5 cm to 22.5 cm with mean 18.2 cm, median and modus of 18.5 cm. The weight ranged from 16 gr to 149 gr, with mean and median 80 gr and modus 89 gr. Succeed of lift net operation to catch Indian Mackerel occurred during last quarter moon phase. The catch of Indian Mackerel is categorised as juveniles and undersized catch. Biomass size spectra identified that less fishing intensity during full moon affect less vulnerability of small fish being caught. This result should be concerned otherwise growth overfishing could not be avoided.